Impact of the PMI Strategy on Persuasive Writing Among Second-Grade Intermediate Female Students (Journal of the College of Basic Education, 2025)
The research aims to identify the "impact of the PMI strategy on persuasive writing among second-grade intermediate female students." To achieve the research objective, the researcher adopted the null hypothesis: "There are no statistically significant differences at the (0.05) level between the performance of the experimental group students who studied the subject of expression by adopting the steps of the PMI strategy, and the performance of the control group students who studied the same subject in the traditional way in the post-test of persuasive writing." The research sample consisted of second-grade intermediate female students in the academic year at Al-Ikhlas Secondary School for Girls, affiliated with the Directorate of Education of Baghdad Al-Karkh III. The experimental group consisted of (32) students who were taught according to the steps of the PMI strategy, and the control group was taught according to the traditional method. The researcher prepared a persuasive writing test consisting of eight essay paragraphs and verified its validity and reliability. After completing the experiment in the first semester of the academic year 2024-2025, the researcher administered the prepared test, and the results showed the superiority of the experimental group students over the control group students.